HSP70 induces liver X receptor pathway activation and cholesterol reduction in vitro and in vivo - Burcin Gungor; Lauri Vanharanta; Maarit Hölttä-Vuori; Juho Pirhonen; Nikolaj H.T. Petersen; Silvia Gramolelli; Päivi M. Ojala; Thomas Kirkegaard; Elina Ikonen (Elsevier, 2019)
Objective: Heat Shock Proteins (HSPs) maintain cellular homeostasis under stress. HSP70 represents a major stress-inducible family member and has been identified as a druggable target in inherited cholesterol-sphingolipid storage diseases. We investigated if HSP70 modulates cholesterol accumulation in more common conditions related to atherogenesis. Methods: We studied the effects of recombinant HSP70 in cholesterol-laden primary macrophages from human blood donors and pharmacological HSP70 upregulation in high-cholesterol diet fed zebrafish. Results: Recombinant HSP70 facilitated cholesterol removal from primary human macrophage foam cells. RNA sequencing revealed that HSP70 induced a robust transcriptional re-programming, including upregulation of key targets of liver X receptors (LXR), master regulators of whole-body cholesterol removal. Mechanistically, HSP70 interacted with the macrophage LXRalpha promoter, increased LXRalpha and its target mRNAs, and led to elevated levels of key proteins facilitating cholesterol efflux, including ATP-binding cassette transporters A1 and G1. Pharmacological augmentation of endogenous HSP70 in high-cholesterol diet fed zebrafish activated LXR and its target mRNAs and reduced cholesterol storage at the whole organism level. Conclusion: These data demonstrate that HSP70 exerts a cholesterol lowering effect in primary human cells and animals and uncover a nuclear action of HSP70 in mediating cross-talk between HSP and LXR transcriptional regulation. Keywords: Cholesterol metabolism, Liver X receptor, Heat shock protein, Human macrophages, Transcriptional regulation